2022
DOI: 10.1186/s13018-022-03254-7
|View full text |Cite
|
Sign up to set email alerts
|

Does cervical curvature affect neurological outcome after incomplete spinal cord injury without radiographic abnormality (SCIWORA): 1-year follow-up

Abstract: Background At present, surgery is the primary clinical treatment for SCIWORA patients, but conservative treatment still plays an important role in patients with incomplete spinal cord injury. As an important index of cervical spine degeneration, cervical curvature has an impact on the prognosis of spinal cord injury patients. This paper studied the prognosis of conservatively treated patients with SCIWORA and the correlation between cervical curvature and neurological prognosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…A review of MRI measurements showed that cord-canal mismatch (a higher spinal cord occupation ratio in the spinal canal) was more important and should be viewed as the underlying mechanism predisposing individuals to SCI [17]. In addition, a report suggests that improving the cervical curvature can positively impact prognosis, as the cervical curvature in patients with total spinal balance can be affected by nonsurgical treatment for CSCI without major bone injury [18].…”
Section: Incidence Of Cscs In Patients With Csci Without Major Bone I...mentioning
confidence: 99%
“…A review of MRI measurements showed that cord-canal mismatch (a higher spinal cord occupation ratio in the spinal canal) was more important and should be viewed as the underlying mechanism predisposing individuals to SCI [17]. In addition, a report suggests that improving the cervical curvature can positively impact prognosis, as the cervical curvature in patients with total spinal balance can be affected by nonsurgical treatment for CSCI without major bone injury [18].…”
Section: Incidence Of Cscs In Patients With Csci Without Major Bone I...mentioning
confidence: 99%
“…Scheer et al 1 reviewed the literature and found a correlation between the variation of radiographic parameters and postoperative health‐related quality of life. Plenty of studies demonstrate that it is vital to restore neutral cervical lordosis and preserve cervical ROM in cervical spine surgery 4–7 . However, for multilevel cervical spondylotic myelopathy (CSM) surgery treatment, cervical biomechanical and kinematics structures may be widely disturbed, bringing more challenges to maintaining cervical alignment and preserving ROM.…”
Section: Introductionmentioning
confidence: 99%